THE LEVEL OF STUDENTS’ READING ACHIEVEMENTS BASED ON MULTIPLE-CHOICE ASSESSMENT IN MAKASSAR - Fathur Rahman Saut Matua Situmorang; Baso Jabu; Geminastiti Sakkir (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
This study aimed to determine the level of students’ reading achievement when assessed using multiple-choice questions. Employing a quantitative descriptive design, the research was conducted at SMPN 40 MAKASSAR in the 2025/2026 academic year and involved 32 eight-grade students selected through cluster random sampling. The instrument consisted of a multiple-choice reading comprehension test developed based on indicators such as identifying the main idea, locating detailed information, interpreting vocabulary in context, making inferences, and determining the authors’ purpose. The data were analyzed using descriptive statistics. The findings showed that the mean scores were 78.75 with a standard deviation of 7.071. These results indicate that students demonstrated a satisfactory level of reading comprehension when assessed through multiple-choice questions, suggesting that this format can effectively measure students’ reading achievement at the junior high school level.